1976
DOI: 10.1107/s056774087600798x
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of BaNiO3

Abstract: The crystal structure of BaNiOa has been determined by single-crystal analysis. The space group is P63/mmc and lattice constants are a= 5.629 (3) and c=4"811 (3) A, with Z= 2. The structure has been refined by the block-diagonal least-squares technique to a final R value of 0-049. The structure is characteristic with linear chains of nickel atoms having a Ni-Ni distance of 2"405 (2) A,; the NiO6 octahedron is trigonally distorted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0
2

Year Published

1977
1977
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(61 citation statements)
references
References 2 publications
2
54
0
2
Order By: Relevance
“…Barium is in a twelve-fold coordination by oxygen. The crystallographic data are as follows: space group: P6 3 /mmc, a = 562.9(3) pm, c = 481.1 (3) pm, Ba at 2d (1/3, 2/3, 3/4), Ni at 2a (0,0,0), O at 6h (0.1462, -0.1462, 0.25) [24], CaNiN was prepared by heating calcium and nickel in an alumina crucible under nitrogen at 1000°C for 10 h. The samples were examined by X-ray powder diffraction and atomic absorption spectroscopy. They contained small amounts of metallic nickel as well as Ca 3 N 2 .…”
Section: Crystal Structures and Sample Preparationmentioning
confidence: 99%
“…Barium is in a twelve-fold coordination by oxygen. The crystallographic data are as follows: space group: P6 3 /mmc, a = 562.9(3) pm, c = 481.1 (3) pm, Ba at 2d (1/3, 2/3, 3/4), Ni at 2a (0,0,0), O at 6h (0.1462, -0.1462, 0.25) [24], CaNiN was prepared by heating calcium and nickel in an alumina crucible under nitrogen at 1000°C for 10 h. The samples were examined by X-ray powder diffraction and atomic absorption spectroscopy. They contained small amounts of metallic nickel as well as Ca 3 N 2 .…”
Section: Crystal Structures and Sample Preparationmentioning
confidence: 99%
“…17 We have prepared two chromium sulfides with 1-D structures, Ba 3 CrS 5 , and Ba 3 Cr 2 S 6 at high pressures and high temperatures. 1 These sulfides, having structures that are closely related to BaNiO 3 , [18][19][20] structure and can be prepared only by high-pressure synthesis method. Reaction conditions of the high-pressure synthesis method are completely different from any other conventional ones using evacuated ampoules or floating CS 2 or H 2 S gases.…”
mentioning
confidence: 99%
“…On the basis of powder work, they reported that BaCoO 3 was isostructural with BaNiO 3. The crystal structure of BaNiO 3 is described in terms of hexagonally close-packed BaO 3 layers and Ni ions located in the oxygen octahedra: these share a pair of opposite faces to form (NiO3),, columns parallel to c. However, BaNiO 3 does not have an ideal hexagonally close-packed arrangement of Ba and O ions, but all the O ions are remarkably close to Ni ions and form a trigonally distorted octahedron; the Ni4+--O distance is much shorter than that expected from the ideal ionic model (Takeda, Kanamaru, Shimada & Koizumi, 1976).…”
mentioning
confidence: 99%